The Role of Strategic Alliances in Promoting the Organization's Leadership Field Study of a Sample of Managers of Travel and Aviation Companies in Dohuk Governorate - Nori, Rang M.; Salman, Dlofan A. (Humanities Journal of University of Zakho, 2014)
The research aimed to investigate the concepts of strategic alliances and entrepreneurial orientation as contemporary concepts that appeared due to of the rapid developments and the appearance of the concept of globalization. Particularly, the study focused on investigating the role of strategic alliancesstyles in supportentrepreneurial orientation. A sample contains 31managers of travel agencies working in the Duhok city. Participants were given questionnaire as a main instrument used for collecting data. mean, standard deviation and linier regression analysis were utilized to analyse the collected data. The results show that all types of strategic alliances play a significant role in supporting entrepreneurial orientation. Overall, it is recommended that firms should pay a great attention to all types of strategic alliances which could consequently affect their entrepreneurial position.